Lipoprotein from the osmoregulated ABC transport system OpuA of Bacillus subtilis: purification of the glycine betaine binding protein and characterization of a functional lipidless mutant. - Kempf, B (1997)
The OpuA transport system of Bacillus subtilis functions as a high-affinity uptake system for the osmoprotectant glycine betaine. It is a member of the ABC transporter superfamily and consists of an ATPase (OpuAA), an integral membrane protein (OpuAB), and a hydrophilic polypeptide (OpuAC) that shows the signature sequence of lipoproteins (B. Kempf and E. Bremer, J. Biol. Chem. 270:16701-16713, 1995). The OpuAC protein might thus serve as an extracellular substrate binding protein anchored in the cytoplasmic membrane via a lipid modification at an amino-terminal cysteine residue. A malE-opuAC hybrid gene was constructed and used to purify a lipidless OpuAC protein. The purified protein bound radiolabeled glycine betaine avidly and exhibited a KD of 6 microM for this ligand, demonstrating that OpuAC indeed functions as the substrate binding protein for the B. subtilis OpuA system. We have selectively expressed the opuAC gene under T7 phi10 control in Escherichia coli and have demonstrated through its metabolic labeling with [3H]palmitic acid that OpuAC is a lipoprotein. A mutant expressing an OpuAC protein in which the amino-terminal cysteine residue was changed to an alanine (OpuAC-3) was constructed by oligonucleotide site-directed mutagenesis. The OpuAC-3 protein was not acylated by [3H]palmitic acid, and part of it was secreted into the periplasmic space of E. coli, where it could be released from the cells by cold osmotic shock. The opuAC-3 mutation was recombined into an otherwise wild-type opuA operon in the chromosome of B. subtilis. Unexpectedly, this mutant OpuAC system still functioned efficiently for glycine betaine acquisition in vivo under high-osmolarity growth conditions. In addition, the mutant OpuA transporter exhibited kinetic parameters similar to that of the wild-type system. Our data suggest that the lipidless OpuAC-3 protein is held in the cytoplasmic membrane of B. subtilis via its uncleaved hydrophobic signal peptide.